3(2z-9)=2z-1

Simple and best practice solution for 3(2z-9)=2z-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2z-9)=2z-1 equation:


Simplifying
3(2z + -9) = 2z + -1

Reorder the terms:
3(-9 + 2z) = 2z + -1
(-9 * 3 + 2z * 3) = 2z + -1
(-27 + 6z) = 2z + -1

Reorder the terms:
-27 + 6z = -1 + 2z

Solving
-27 + 6z = -1 + 2z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-2z' to each side of the equation.
-27 + 6z + -2z = -1 + 2z + -2z

Combine like terms: 6z + -2z = 4z
-27 + 4z = -1 + 2z + -2z

Combine like terms: 2z + -2z = 0
-27 + 4z = -1 + 0
-27 + 4z = -1

Add '27' to each side of the equation.
-27 + 27 + 4z = -1 + 27

Combine like terms: -27 + 27 = 0
0 + 4z = -1 + 27
4z = -1 + 27

Combine like terms: -1 + 27 = 26
4z = 26

Divide each side by '4'.
z = 6.5

Simplifying
z = 6.5

See similar equations:

| mn^2-2n= | | 2q-1=20 | | 8a-(a-7)=22 | | 5(x+3)-4whenx=9 | | 9x^2+18x-79=0 | | -(4y+3)-(3y-8)=4 | | m+48=32 | | 5(x+3)=35-15 | | 12/40-35/40 | | -1/3p=7/8 | | 5(x+3)-4x=9 | | 6(n-2)-12=18 | | 9x+2(3x+7)=-29 | | 2y=-3x+38 | | 7*3-2y=24 | | 3(x/3-2)=9+3 | | 3(2x-1)-(6x-5)=-7 | | y/3+2=4 | | 6X^2-14X=4420 | | y/2-2=-4 | | 9x2+10/2 | | 4[5(w+3)-(w+1)]=7(3+w) | | 2100=2700-.03x | | 4y^2=9 | | t=5n-7 | | 23/10-17/8 | | 10x-4x+12=2(3x+6) | | 4x-2-(2x+3)=13 | | -2z+1=5 | | H(t)=-16t^2+128t | | 2-(3x-5)=34 | | 2x^2+16+42=0 |

Equations solver categories